Complementarity in the Central Area of Mexico: The Spatial Interaction between Economic Activity and Connectivity - Claudia Tello; Amilcar Morales; Mario Ledesma (Prostranstvennaâ Èkonomika)
Road connectivity is essential for regional development, which stems from the complementarity and economic diversification of Mexico’s regions. Upgraded road infrastructure boosts access to markets, resources, and services, improving population mobility and lessening economic disparities between urban and rural zones. This article examines how municipalities in the central region connect with each other and what their main economic activities are, based on employment data. Spatial statistics and correspondence analysis were used to assess indicators highlighting the importance of both connectivity types for improved road network function after the 2023 expansion. The study found a strong correlation between road network development and spatial structure. This resulted in improved local, regional, and inter-city connections, enhancing connectivity in the study area. The study underscores the diverse economic activities and heterogeneous patterns across urban, peri-urban, and rural areas. Our research covers 252 municipalities across eleven Mexican states. The 252 municipalities studied cover 108,627.48 kilometers of the 2023, representing 12.41% of the national network. This study uses readily available geospatial data, including the 2023 National Road Network. We also used data from the 2023 National Statistical Directory of Economic Units, the 2020 Population and Housing Census, and the 2022 Agricultural Census